Restriction of salt, alcohol and coffee intake and Ménière’s disease: insight from Mendelian randomization study - Gao, Wei; Ma, Pengwei; Wang, Zi; Guo, Jianing; Lun, Yuqiang; Wang, Weilong; Yuan, Hao; Li, Siyu; Liang, Rui; Lu, Lianjun (Frontiers in Nutrition, 2024)
Background: Restricting salt, caffeine, and alcohol intake is commonly recommended as a first-line treatment for patients with Mé niè re's disease (MD). However, it remains unclear whether these interventions effectively improve symptoms of MD. Therefore, we conducted a bidirectional twosample Mendelian randomization (MR) analysis to evaluate the relationship between these dietary modifications and MD. Methods: Summary statistics for salt added to food, alcohol consumption, coffee consumption, and MD were sourced from the UK Biobank, GSCAN, and the FinnGen study, involving up to 941,280 participants. The main analyses were performed using the random-effects inverse-variance weighted (IVW) approach and were complemented by four additional methods. Multiple sensitivity analyses were performed to validate the findings, and both forward and reverse MR analyses were employed to address potential reverse causality bias.Results: The primary MR results using the IVW method revealed that salt added to food (OR = 0.719, 95% CI: 0.429-1.206; P = 0.211), alcohol consumption (OR = 0.834, 95% CI: 0.427-1.628; P = 0.595), and coffee consumption (OR= 0.852, 95% CI: 0.555-1.306; P = 0.461) were not significantly correlated with MD. In reverse analysis, no evidence of significant effect was found from MD to salt added to food (OR = 1.000, 95% CI: 0.993-1.007; P = 0.957), alcohol consumption (OR = 0.998, 95% CI: 0.987-1.008; P = 0.682), and coffee consumption (OR = 0.998, 95% CI: 0.985-1.011; P = 0.72).Conclusion: This MR analysis did not identify convincing evidence to support the idea that restricting salt, caffeine, and alcohol intake is beneficial for the treatment of MD.